State and revolution in Finland - Alapuro, Risto, 1944- (Historical materialism book series, 2019)
By analysing the experience of Finland, Risto Alapuro shows how upheavals in powerful countries shape the internal politics of smaller countries. This linkage, a highly topical subject in the twenty-first century world, is concretely studied by putting the abortive Finnish revolution of 1917-18 into a long historical and a broad comparative perspective. In the former respect the revolution appears as a tragic culmination in the unfolding of a small European state. In the latter respect it appears as one of those crises that new states experienced when they emerged from the turmoils of the First World War. This second edition includes a new Postscript.